Grounded theory research on the factors that lead to doctor moral hazard - Yaohui; Jiankun; Xifeng; Quanlong; Xinchun (Saúde e Sociedade, 2021)
Moral hazard clearly exists among doctors, and it has a dramatic impact on doctor-patient relationships, medical costs and medical risks. This study explored the factors that lead to doctor moral hazard, as well as the interrelationships and internal regularity of these factors. This study takes doctor moral hazard as the research content and the inducing factors as the core theme, conducting grounded theory research on the causes of doctor moral hazard. Scientific understanding of doctor behavior would facilitate the prevention and control of doctor moral hazard behavior. This study used the principles and methodology of Glaser and Strauss’s grounded theory. Theoretical and snowball samplings were used to identify 24 subjects. Semi-structured in depth interviews were conducted with each subject. Themes were identified through substantial (open) coding and theoretical coding. The factors that lead to doctor moral hazard were categorized into five dimensions, i.e. motivation, opportunity, self rationalization, exposure and punishment. These five factors influence each other, forming the inducing mechanism of doctor moral hazard. This will provide useful theoretical support and method guidance for the follow-up prevention and control of moral hazard for doctors.